ANALISIS PENGARUH PROMOSI KESEHATAN DENGAN MEDIA KOMIK DAN VIDEO TERHADAP PENGETAHUAN TENTANG TUBERKULOSIS PADA SISWA SMPN 17 KOTA TANGERANG SELATAN TAHUN 2020 - Isna Ari Fadila, (2021)
Tuberculosis disease or known as TBC is a transmitting disease caused by Mycobacterium tuberculosis bacteria. TBC disease can infect all genders and age groups from kids to adults. This is proven from all case of TBC that has been recorded in Indonesia, which 11,9% from all case originated from 0-14 years old group. The purpose of this research is to analyze the effects of health promotion with video and comic media toward knowledge of TBC in students and also to find out effectivity degree from media that had been used. This research uses quasi-experimental with pretest-posttest non-equivalent group design. The sample was taken with a stratified random sampling technic with a total of 164 students. Data analysis result with Wilcoxon signed ranks test and Mann Whitney show there are differences in TBC's knowledge in students before and after health promotion with comic and video media done (p-value 0,000) and also effectivity difference of health promotion with comic media (p-value 0,004). Health promotion with video media much effective when compared to comic media. Comic and video can utilize simultaneously as a health promotion method with adjusting to target characteristics. For future researchers, it is advisable to use a different type of media, as well as involving other grade levels.